LITERASI BERBAHASA BALI DALAM KEGIATAN KAMIKEBALI (KAMIS KEBUDAYAAN BALI) DI SMPN 2 SEMARAPURA - Puspita Dewi, Ni Nengah Vera (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
The existence of the Balinese language is increasingly threatened, especially when there are more opportunities for language competition to occur. When tourism began to bloom in Bali, the local language competed with foreign languages that entered Bali, especially English. Quite a number of Balinese people think that learning a foreign language is far more economically profitable than learning Balinese. This has caused many local Balinese to choose to teach foreign languages to their children rather than regional languages. The existence of the Balinese language has not yet become extinct, but this has led to a massive reduction. More and more Balinese young people do not understand the rules for using the Balinese language properly and correctly, such as sor singgih basa, along with its spelling and how to write it. In addition, there is also blindness to other skills related to Balinese, such as mageguritan, masatua, mapidarta, Balinese ngorti, macecimpedan, and so on. Gradually, in the midst of the hustle and bustle of tourism, the Balinese began to feel unsure about their identity. Born and living in Bali, I am unable to use the proper and correct Balinese language. Since then, efforts have appeared that lead to the re-literacy of Balinese, starting at the family, school, community, and even government bureaucratic levels. This study aims to describe KAMIKEBALI literacy at SMP Negeri 2 Semarapura, which is part of a broader Balinese language literacy effort. This research method is qualitative, with a concentration on field research. KAMIKEBALI activities at SMPN 2 Semarapura are a form of linguistic literacy that includes the stages of introduction, application, and stabilization or civilization.